Múltiplas inteligências, criação e interatividade no ambiente virtual de aprendizagem edulivre - Borges, Leonidas Leão (2010)
The aim is to verify how the Virtual Environment for Learning (VEL), fulfilled in the Edulivre Project scope, enhances the development of multiple intelligences in children from 7 to 9 years old. The VEL was developed by the Laboratory of Digital Video Applications of the Federal University of Paraíba in partnership with two schools in João Pessoa, PB. This Project intends to develop a VEL for learners of the first elementary school year to take part in the cyberspace as micro-actors of the new cognitive ecology which encompasses them, therefore, allowing these learners the chance to appropriate new multi-mediatic and multi-sensorial languages as well as the original forms to communicate via digital technologies and their information and communication devices. The VEL conception had as fundamentals Jean Piaget´s interactionist ideas ones widened by means of the new scientific contributions proposed in the framework of Howard Gardner s multiple intelligences. As to the methodology, it was used the research-action through a participative and interventional experience involving the groups of students, teachers, software programmers and designers. It was part of an open, free, fruitful and private context which is important for the authorship of hypermedia materials and for the implementation of a computational model with tools and functionalities suitable for both the intellectual profile of the inter-agents and the cultural context of the schools. These are essential characteristics to make the VEL a rich, useful and effective pedagogical tool in order to enhance the multiple intelligences of the seven to nine year old learners. The students´ and teachers´ group produced 159 contents and they implemented functionalities, such as: comments, chat, video sharing, digital ombudsperson and tool for evaluating the learners´ intellectual profile. The accomplished analysis concerning the contents, tools and functionalities identified, potentially, several combinations involving the following intelligences: the linguistic, the musical-rhythmic, the logic-mathematical, the spatial, the bodily-kinesthetic, the intrapersonal, the interpersonal and the naturalistic. With reference to the teachers´ participation in the process of digital technologies production, new logics, methodologies and aesthetic, pedagogical and communicational possibilities were offered to them. These emerged as an agenda of changes of their communicational praxis emphasizing competences not only for the operational domain of technologies, but also for the capacity of their use in learning contexts requiring from the teachers both a technical and a technical-pedagogical formation. In relation to the computing science bachelors, besides the linguistic, logical-mathematical and spatial capacities which are usually highlighted in their formation, their personal intelligences valued the environment calling their attention for the human dimension of their mission. Furthermore, this displaced the focus on the object and put it on the project helping to build an ergonomic, functional and human relationship among the learners. In this way, the computers pointed out their humanistic formation and prepared these experts to develop their personal abilities aiming to act not only as emotionally competent professionals but enabled them to understand the conditions of their work in the world and in society.